Solid lubricant nanocoating’s based on magnesium compounds - Shchepetov, V.V.; Fialko, N.M.; Bys, S.S. (Problems of Tribology, 2026)
The results of studies of friction and wear of detonation composite nanocoating’s based on the ternary compound aluminum-magnesium-boron under test conditions with constant load in the sliding velocity field are presented. Their structural-phase composition and passivating complex of surface oxide structures are determined using modern physical analysis methods. It is established that the parameters of wear intensity and friction coefficients are minimized due to the set of surface structures that regenerate a stable self-lubricating structured layer under friction conditions. Factors that influence the formation of dynamic equilibrium of a self-lubricating layer that has an effective ability to self-repair are determined. At the same time, a continuous protective layer screens the processes of molecular-adhesive interaction and blocks the development of unacceptable destruction phenomena.